2012
DOI: 10.1186/1743-7075-9-79
|View full text |Cite
|
Sign up to set email alerts
|

Dietary glycemic index and glycemic load in relation to HbA1c in Japanese obese adults: a cross-sectional analysis of the Saku Control Obesity Program

Abstract: BackgroundDietary glycemic index or load is thought to play an important role in glucose metabolism. However, few studies have investigated the relation between glycemic index (GI) or load (GL) and glycemia in Asian populations. In this cross-sectional analysis of a randomized controlled trial, the Saku Control Obesity Program, we examined the relation between the baseline GI or GL and glycemia (HbA1c and fasting plasma glucose [FPG] levels), insulin resistance (HOMA-IR), β-cell function (HOMA-β), and other me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
0
6
1
Order By: Relevance
“…However, in this cross-sectional analysis of healthy postmenopausal women, higher cereal fiber intake and lower starchto-cereal fiber and carbohydrate-to-cereal fiber intake were associated with lower concentrations of HbA1c. Among healthy adults, 2 cross-sectional studies found no association between whole grain intake and HbA1c concentrations, but 1 among obese Japanese adults found a positive association between GL (not GI) and HbA1c concentrations, which we did not observe in our study (10,39,40). Among adults with T2D, a meta-analysis of 10 randomized controlled trials of fiber supplementation lasting from 3 to 12 wk found that participants in the fiber intervention arm, overall, had a reduction in HbA1c of 0.26% more than the reduction in control participants (41).…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…However, in this cross-sectional analysis of healthy postmenopausal women, higher cereal fiber intake and lower starchto-cereal fiber and carbohydrate-to-cereal fiber intake were associated with lower concentrations of HbA1c. Among healthy adults, 2 cross-sectional studies found no association between whole grain intake and HbA1c concentrations, but 1 among obese Japanese adults found a positive association between GL (not GI) and HbA1c concentrations, which we did not observe in our study (10,39,40). Among adults with T2D, a meta-analysis of 10 randomized controlled trials of fiber supplementation lasting from 3 to 12 wk found that participants in the fiber intervention arm, overall, had a reduction in HbA1c of 0.26% more than the reduction in control participants (41).…”
Section: Discussioncontrasting
confidence: 84%
“…Conventional measures of carbohydrate quality such as total fiber, cereal fiber, whole grains, and low glycemic index (GI) and glycemic load (GL) intakes have been consistently associated with a lower risk of T2D (5)(6)(7)(8). GL has been inversely associated with adiponectin concentrations among US men (9) and positively associated with HbA1c concentrations in Japanese adults (10). Total fiber intake has been inversely associated with CRP (11)(12)(13) concentrations in a nationally representative US study and in 2 other cohorts of US adults, but was not associated with CRP in a study among postmenopausal women (14).…”
Section: Introductionmentioning
confidence: 99%
“…Considering that rice is a high GI food and that it is the major source of carbohydrates in Japanese diets, the current result seems reasonable, as the dietary GL reveals both the quantity and quality of carbohydrates in diets. A cohort study in Chinese women also reported a positive association between the dietary GL and the risk of diabetes [ 14 ], and a recent cross-sectional study of obese males and females in Japan reported an association between the dietary GL and the HbA1c level [ 37 ]. No association was observed between the dietary GL and the risk of diabetes among men.…”
Section: Discussionmentioning
confidence: 99%
“…The average dietary GI was 66 ± 5, and the average dietary GL was 79 ± 17 (1000 kcal). They showed that GI was not associated with HbA1c, but GL was positively associated with HbA1c [ 62 ]. For increasing quartiles of GI, the adjusted mean HbA1c were 6.3%, 6.7%, 6.4% and 6.4% ( p for trend = 0.991); whereas, for increasing quartiles of GL, the adjusted mean HbA1c were 6.2%, 6.2%, 6.6% and 6.5% ( p for trend = 0.044).…”
Section: Are All Carbohydrates the Same? Does Carbohydrate Type Mamentioning
confidence: 99%